Formula approaches for market access negotiations - Francois, Joseph (2003)
Provides some detail on the current market access landscape. Highlights important issues related to tariff peaks, unbound tariffs and gaps between bound and applied rates. Considers some formula-based approaches and develops the concept of flexible formula approaches as well. Focuses on some of the design issues associated with the use of a flexible formula approach.